Karakteristik Bakteri Pelarut Fosfat pada Tingkat Kematangan Gambut di Kawasan Hutan Lindung Gunung Ambawang Kabupaten Kubu Raya - Riza Linda, Wila Friska, Siti Khotimah, (Universitas Tanjungpura, 2015)
Bacterial phosphate solvent is bacteria that have role in enrichment of soil. Origin material and formation ofpeat soil have correlation with the maturity and the level of fertility of peat soil. The recent research aimed to find out genus and density of bacterial phosphate solvent at the level of maturity of different peat soil in protected forest areas of Ambawang Mountain in District of Teluk Pakedai, Kubu Raya Regency. The isolation of bacterial was conducted by using the media of pikovskaya and pour plate method, whereas bacterial density calculation was done by total plate count method. The research finding showed that there were five genera of bacterial phosphate solvent, namely; Acinetobacter, Chromobacterium, Flavobacterium, Micrococcus, and Stapylococcus. There was no different of the total density of bacterial colonies phosphatesolvent in fibric, hemic, and sapric.